2019
DOI: 10.1177/1040638719832340
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the CoaguChek-XS portable prothrombin time point-of-care analyzer for horses

Abstract: In horses, gastrointestinal (GI) disorders are the main cause of disseminated intravascular coagulation (DIC), a potentially life-threatening condition. Large colon volvulus, colitis, and strangulating small intestinal lesions are the most common GI conditions that cause DIC in horses, 4,12 but DIC is also reported in septicemia, snakebites, rhabdomyolysis, and diffuse clostridial myonecrosis. 11,13,16,19,21,22 Significantly prolonged PT was reported in 58% of horses with acute GI crisis-associated DIC, 12 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Therefore, the sensitivity and specificity of CCX were not proven. Nevertheless, the previous studies reported sensitivity and specificity of this device as 92% and 56%, respectively, in dogs [ 12 ] and 50% and 74%, respectively, in horses [ 21 ]. Thus, we do not recommend using CCX for diagnosing coagulation abnormalities in cats.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, the sensitivity and specificity of CCX were not proven. Nevertheless, the previous studies reported sensitivity and specificity of this device as 92% and 56%, respectively, in dogs [ 12 ] and 50% and 74%, respectively, in horses [ 21 ]. Thus, we do not recommend using CCX for diagnosing coagulation abnormalities in cats.…”
Section: Discussionmentioning
confidence: 96%
“…Accuracy of PT measurement using the CCX was reported in human [ 17 - 19 ], horse [ 21 ], and dog [ 12 ]. The previous studies found that the CCX was reliable for screening dogs when the PT was normal [ 12 ], while it was potentially specific and quite sensitive for detecting abnormal hemostasis in horses [ 21 ]. However, the accuracy of the CCX for PT measurement in cats and normal ranges was not evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…CoaguChek ® -XS, was shown to accurately and precisely measure PT in domestic dogs and horses (Newbould and Norman, 2013;Kelmer et al, 2014;Berlin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%